Zooplankton of the Black Sea and the Eastern Mediterranean: Similarities and dissimilarities - KOVALEV, A.V.; MAZZOCCHI, M.G.; SIOKOU, I.; KIDEYS, A.E. (Mediterranean Marine Science, 2001)
A synthesis of data on abundance and biomass of zooplankton in the Eastern Mediterranean (EMED) and the Black Sea shows major differences in the composition and structure of pelagic communities in the two basins. Few Mediterranean planktonic animals have invaded and acclimatised in the Black Sea. The great bulk of Black Sea species is represented by coastal inhabitants that spread throughout the whole basin. This process has been called “neritization” of the Black Sea fauna. Peculiarities in zooplankton assemblages of the Black Sea have been further strengthened over the last few decades due to increasing eutrophication and the massive invasion of the ctenophore Mnemiopsis leidyi. The relative contribution of copepods, cladocerans, chaetognaths, and appendicularians to total zooplankton biomass has notably decreased , whereas gelatinous groups (mainly represented by Mnemiopsis and Aurelia aurita) contributed up to 99% of total wet weight in 1995 in the Black Sea. The basic features of planktonic fauna in the Black Sea are mainly due do the geo-morphological characters of the basin and the limited exchanges with the EMED, that are confined to the surface-subsurface layers in the Dardanelles and Bosphorus Straits. However, the dramatic changes that recently occurred in the structure of zooplankton assemblages seem to have been caused by heavy anthropogenic impact on the pelagic system.